Expression of the human antimicrobial peptide β-defensin-1 is repressed by the EGFR-ERK-MYC axis in colonic epithelial cells. Issue 1 (December 2018) - Bonamy, Clément; Sechet, Emmanuel; Amiot, Aurélien; Alam, Antoine; Mourez, Michael; Fraisse, Laurent; Sansonetti, Philippe; Sperandio, Brice
Abstract The human β-defensin-1 (HBD1) is an antimicrobial peptide constitutively expressed by epithelial cells at mucosal surfaces. In addition to its microbicidal properties, the loss of HBD1 expression in several cancers suggests that it may also have an anti-tumor activity. Here, we investigated the link between HBD1 expression and cancer signaling pathways in the human colon cancer cell lines TC7 and HT-29, and in normal human colonic primary cells, using a mini-gut organoid model. Using available datasets from patient cohorts, we found that HBD1 transcription is decreased in colorectal cancer. We demonstrated that inhibiting the Epidermal Growth Factor Receptor (EGFR) increased HBD1 expression, whereas activating EGFR repressed HBD1 expression, through the MEKK1/2-ERK1/2 pathway that ultimately regulates MYC. We finally present evidences supporting a role of MYC, together with the MIZ1 coregulator, in HBD1 regulation. Our work uncovers the role and deciphers the function of the EGFR-ERK-MYC axis as a repressor of HBD1 expression and contributes to the understanding of HBD1 suppression observed in colorectal cancer.